La resistencia a la tracción de la mecha está asociada con las características textiles de la fibra en alpacas negras y marrones - Pinares, Rubén (2025)
The aim of this study was to determine the correlation between the staple strength and the textile characteristics of black and brown fibres, as well as to evaluate the influence of colour, breed, location, age, and sex of alpaca on the staple strength properties. Staple strength was measured with the Staple Length & Strength instrument. Fibre characteristics were measured using an Optical-based Fibre Diameter Analyzer (OFDA 2000). Data did not show a normal distribution, as verified by the Shapiro-Wilk normality test. Spearman’s rank correlation coefficients between staple strength and fibre textile characteristics were calculated. The influence of colour, breed, location, age, and sex of alpacas on the staple strength properties were analysed separately by the Kruskal-Wallis rank sum test (α=0.05). The highest correlation was observed between peak force position and staple length (rs = 0.99), as well as significant positive correlations for staple strength with peak force (rs = 0.53), with fibre curvature (rs = 0.42), and with comfort factor (rs = 0.20). However, there were negative correlations for staple strength with spinning fineness (rs = -0.20) and standard deviation of mean fibre diameter (rs = -0.23). The fibre colour and the sex of the alpaca did not influence on the staple strength and peak force; location did not influence on the staple strength (p>0.05). However, the age category and the breed influenced the staple strength and staple length (p<0.05). Staple strength increased with age, ranging from 16.75 to 20.10 N/ktex for young animals (milk teeth and 2-teeth categories) and 38 N/ktex for 4-teeth animals. Suri fibre is longer and has a lower staple strength (13.4 N/ktex) compared to Huacaya fibre (29.5 N/ktex). In conclusion, the favourable negative correlations between textile and physical properties would allow a reduction in the standard deviation of MFD and spinning fineness, while improving staple strength in black and brown alpacas.